Clinical management of pruritus - Ständer, Sonja; Weisshaar, Elke (Journal der Deutschen Dermatologischen Gesellschaft, 2015)
The care of patients with chronic pruritus as a symptom of a wide variety of underlying diseases continues to confront dermatologists with diagnostic and therapeutic challenges. However, a structured history and a physical examination may already substantially help in narrowing down the number of potential differential diagnoses. Apart form reducing the intensity of pruritus, identification and appropriate treatment of the underlying disease are important needs of patients. If these goals doesn't lead to improvement of itch, current guidelines provide a number of topical and systemic therapies for symptomatic treatment. Various skin lesions (for example, xerosis caused by irritant substances, secondary scratch lesions) prompt patients to consult a dermatologist, but most cases require an interdisciplinary therapeutic approach to identify potential internal medicine, neurologic, or psychosomatic aspects. Although great strides have been made in basic research, specific therapies are still rare, and a precise knowledge of the legal framework for the implementation of guidelines (for example, off-label use) is essential. This CME article gives an overview of the causes of and treatment options for chronic pruritus and discusses both advances in basic research as well as progress in clinical knowledge.
Published online: 10.9.2014
Gesehen am 02.05.2017